The Effect of Parents' Education Level and Learning Motivation on Student's Biology Learning Achievement Class XI SMA Negeri I Panai Hulu - Linda Safitri; Zunaidy Abdullah Siregar (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to determine the effect of parental education level and learning motivation on biology learning achievement of class XI students of SMA Negeri I Panai Hulu. This type of research uses multiple regression analysis studies and was carried out at SMA Negeri I Panai Hulu with a purposive sampling technique for class XI MIPA 1 with 35 students, XI MIPA 2 with 36, and XI MIPA 5 with 31 students. The results showed Calculation of hypothesis testing using the Chi-Square test obtained a significant value of 0.000 less than 0.05. Parents' Education Level and Learning Motivation Influence on Student Achievement in Class XI SMA Negeri I Panai Hulu Year.